Essential roles for four cytoplasmic intermediate filament proteins in Caenorhabditis elegans development - Karabinos, Anton (The National Academy of Sciences, 2001)
The structural proteins of the cytoplasmic intermediate filaments (IFs) arise in the nematode Caenorhabditis elegans from eight reported genes and an additional three genes now identified in the complete genome. With the use of double-stranded RNA interference (RNAi) for all 11 C. elegans genes encoding cytoplasmic IF proteins, we observe phenotypes for the five genes A1, A2, A3, B1, and C2. These range from embryonic lethality (B1) and embryonic/larval lethality (A3) to larval lethality (A1 and A2) and a mild dumpy phenotype of adults (C2). Phenotypes A2 and A3 involve displaced body muscles and paralysis. They probably arise by reduction of hypodermal IFs that participate in the transmission of force from the muscle cells to the cuticle. The B1 phenotype has multiple morphogenetic defects, and the A1 phenotype is arrested at the L1 stage. Thus, at least four IF genes are essential for C. elegans development. Their RNAi phenotypes are lethal defects due to silencing of single IF genes. In contrast to C. elegans, no IF genes have been identified in the complete Drosophila genome, posing the question of how Drosophila can compensate for the lack of these proteins, which are essential in mammals and C. elegans. We speculate that the lack of IF proteins in Drosophila can be viewed as cytoskeletal alteration in which, for instance, stable microtubules, often arranged as bundles, substitute for cytoplasmic IFs.